Awareness and oral health related quality of life (OHRQoL) in patients with dental implants compared to tooth supported FPD: A questionnaire study - Ronak P. Parmar; Gaurav V. Bakutra; Shivlal L. Vishnoi; Priyadarshini Nadig; Rutvik Rana (Elsevier, 2024)
Background: Recently researches in the field of dental implantology have increased, in spite of that very limited knowledge is available to the patients about dental implants as an option for replacement of missing teeth. Goal of replacement of missing teeth is not only functional rehabilitation but overall improvement in quality of life of the patient. Aim: To assess the awareness of dental implants and to compare oral health related quality of life (OHRQoL) in patients treated with implant supported fixed prosthesis (ISPs) and teeth supported fixed prosthesis (FPDs). Methods: & Material: General implant awareness questionnaire was used to assess the awareness of dental implants in 500 participants. Oral health impact profile (OHIP) questionnaire was used to compare OHRQoL between 300 patients treated with ISPs and 300 patients treated with FPDs. Statistical analysis: Sample size was taken to estimate difference between groups at 30 % & 80% power and 5% risk. IBM SPSS 20 (SPSS Inc., Chicago, IL) was used for statistical analysis. Chi square test and independent t- test was used to find statistical difference between variables. Results: 27.2% participants were aware about dental implants. 74.4% participants agreed that missing teeth should be replaced with prosthetic options. Dentists were primary source of knowledge (66%) of dental implants for patients. Parameters like functional limitations, psychological discomfort and pain during mastication were significantly (p < 0.05) higher in FPDs compared to implant supported prosthesis. Conclusions: Awareness of dental implants in general population needs to be increased. Functional and psychological comfort was significantly higher in ISPs compared to teeth supported FPDs.